Review of the bamboo-feeding genus Agrica Strand (Hemiptera: Cicadellidae: Deltocephalinae), with description of two new species from China - Luo, Qiang; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2018)
The bamboo-feeding leafhopper genus Agrica Strand (Cicadellidae: Deltocephalinae) is reviewed. Two new species, A. bisubula sp. nov. and A. longispina sp. nov. from China (Guizhou), are described and illustrated. The male genitalia of A. arisana (Matsumura, 1914) are described for the first time. A key is provided to distinguish known species of the genus.